Tajikistan Country Economic Update, Fall 2018 : Rogun HPP - Potential Resource for Building Human Capital - World Bank Group (World Bank, Washington, DC, 2019)
This edition of the Tajikistan Country Economic Update (CEU) is part of a semiannual series designed to monitor socioeconomic developments in Tajikistan. It presents an analysis of political, economic, and social developments, as well as the progress of and challenges with the implementation of structural reforms in 2018. It also includes a special section highlighting human capital development in Tajikistan.